Early menarche and breast cancer risk: a systematic review and meta‑analysis of 74 case–control studies - Fui Ling, Voon; Edmund Ui Hang, Sim (Springer Nature, 2026)
Purpose: Early menarche is a known risk factor for breast cancer, as established by the Collaborative Group on Hormonal Factors in Breast Cancer in a 2012 reanalysis of data from forty-seven global epidemiological studies. Given recent changes in the average age at menarche, it is important to re-evaluate this association in the context of the past decade. This metaanalysis aimed to examine the relationship between early menarche, particularly before age 13, and female breast cancer risk by analyzing recently published observational studies and exploring this relationship across different regions of the world. Methods: Case–control studies published between January 2014 and February 2025 were systematically searched in Pub- Med, ScienceDirect, Scopus, and Google Scholar. Early menarche was defined as < 13 years. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using common-effect models when heterogeneity was low (I2 ≤ 30%) and random-effects models when heterogeneity was significant (I2 > 30%). Publication bias was assessed using Egger’s test. Results Overall, results of the present meta-analyses show an increased association between menarche age < 13 and the risk of female breast cancer (OR = 1.15 [95% CI: 1.08 – 1.24]). Also, an increased association with breast cancer risk was found in the subgroup of menarche age < 12 (OR = 1.27 [95% CI: 1.09 – 1.48]). Lower OR was found in subgroup of menarche age ≥ 13 (OR = 0.89 [95% CI: 0.85 – 0.94]). For the geographical region subgroups, increased associations between menarche age < 13 and risk of breast cancer were found in Europe (OR = 1.15 [95% CI: 1.07 – 1.25]), North America (OR = 1.07 [95% CI: 1.03 – 1.11]), Oceania (OR = 1.15 [95% CI: 1.02 – 1.30]), and West Asia (OR = 1.70 [95% CI: 1.15 – 2.52]). Both population-based and hospital-based study designs demonstrated higher ORs for the association between menarche age < 13 and the risk of female breast cancer. Conclusions: This meta-analysis found a modest but statistically significant association between menarche before age 13 and increased breast cancer risk worldwide, while women who experienced menarche at age 13 or older had a lower risk. The association varied by region, with relatively higher odds observed in West Asia, Europe, Oceania, and North America. These results indicate an association rather than causation and are limited by the observational nature of the included studies.